The silent but powerful communication of the physical environment of Nkozi campus of Uganda Martyrs University - Otaala, Laura Ariko (African Journals Online (AJOL), 2019)
The purpose of this research was to find out what Uganda Martyrs University students think about the physical environment of the Nkozi campus, which is the main campus of the university with a view to find out if that factor can be used to market the university. Two sets of examination papers (one for second year and the other for first year students) were identified from the registry archives of the university because of their relevance to the topic of research. Initially, there was no certainty about the contents of these documents, but the titles of the pieces of work were suggestive enough to qualify them for selection. The documents were analysed using thematic analysis procedures. The findings indicate that most of the students have positive things to say about the beauty of their campus. In terms of student university selection process, the information found is very useful for Uganda Martyrs University in developing a marketing strategy that can be extended as far as senior one students. Since campus visits have been found to attract many students to specific universities, Uganda Martyrs University could develop a campus visit programme in which parents, potential students and other interested persons can experience the beauty of Nkozi campus. The current students could also be used to advertise the university since they know what the university can offer apart from the beautiful campus. It is recommended that Uganda Martyrs University develop a marketing strategy that has campus visits on top of the list of strategies to be adopted in increasing student intake.